Students’ Divergent Thinking Ability in Finishing Economics Mathematical Test Using CEM-Learning (C-Learning, E-Learning, M-Learning) at Universitas Pamulang - Ibnatur Husnul, Nisak Ruwah; Hasanah, Yenny Marinatul (Universitas Negeri Makassar, 2019)
This research aims to describe the divergent thinking ability of students in economic mathematics learning through CEM learning (C-learning, E-learning, M-learning) at Universitas Pamulang which supplies blended learning at Accounting Department, Faculty of Economy. The components used to find out the students’ ability of divergent thinking are fluency, flexibility, originality, and elaboration. This research applies qualitative approach by using descriptive method. The subjects of this research are accounting students who are taking Economic Mathematics, which uses CEM Learning (c-learning, e-learning, and m-learning) at Universitas Pamulang. The samples are taken by purposive sampling method. The data are taken by giving them Economics Mathematical test, analysing the tests’ results, grouping students to be interviewed related to the tests’ results. The interview is aimed to clarify the test results related to problem solving the economic mathematics test in divergent thinking. The data are analyzed by using triangulation technique. The findings show that CEM-learning (c-learning, e-learning, and m-learning) in students’ initial ability is fairly good. This is proven by the results of economic mathematical test in the, which are in the intermediate level, which was to formulate more than one ways to finish statistical test or problem. However, they were not able to answer on their ways. The components absorbed were fluency, originality, and elaboration